의료인 치과위생사의 전문능력 향상을 위한 치위생학과 교육과정 제안 - 이은선; Eun-sun Lee; 정재연; Jae-yeon Jung; 하정은; Jung-eun Ha; 황수정; Soo-jeong Hwang; 황윤숙; Yoon-sook Hwang (Han'guk Ch'iwisaeng Hakhoe chi, 2018)
Objectives: The purpose of this study was to propose contents of a curriculum and training program for dental hygienists as medical professionals by surveying the opinions of clinical dental hygienists and dental hygiene professors. Methods: The subjects were 192 clinical dental hygienists and 193 dental hygiene professors. They answered questionnaires that consisted of grading each task based on its importance: a) for dental hygiene students to learn, b) to perform autonomously in clinical practice, and c) the expectancy of the task to change when dental hygienists become medical professionals. Data analysis was performed using an independent sample T test to capture differences between clinical dental hygienists and dental hygiene professors. The terms in the answers of open-ended questionnaires were extracted. We used R 3.5.0, R Recommender, and Wordcloud software packages. Results: Calculus removal had the highest scores for dental hygiene students to learn and expectancy to change when dental hygienists become medical professionals. Physiotherapy of temporomandibular disorders (TMD), planning, performing, and assessment of community oral health programs had the lowest scores in autonomy in clinical practice. The dental hygiene professors gave higher scores in most of the tasks for dental hygiene students to learn, autonomy in clinical practice, and expectancy to change, than did clinical dental hygienists. Cardiopulmonary resuscitation (CPR), job ethics, and communication were the most frequently mentioned terms in the training as medical professionals program contents. Conclusions: In the future, it will be necessary to study the curriculum to improve the proficiency of dental hygienists as medical professionals.